The Effectiveness of Health Education: Early Sex Education on Mothers' Level of Knowledge in Providing Sex Education to School Age Children 7-12 Years - Hapsari, Dina Carolina; Ningsih, Ratna; Yeti, Yeti; Sulastri, Titi (Journal Of Health Science (Jurnal Ilmu Kesehatan), 2024)
Sex education for children is an effort so that children can learn about gender and also how to protect it, both in terms of crime, cleanliness and safety. This research was conducted with the aim of providing mothers with sex education starting at an early age. Researchers carry out research at the school stage at the age of 7-12 years, because at this stage children will always want to know about something and are also able to receive information correctly and apply it. Regarding this, health education is given to mothers because as a mother she must have good knowledge to teach sex education to her child, with the aim that the child can learn sex education correctly and it will not have a negative impact on him. The writing of this research uses a quantitative research method with a descriptive analysis method which aims to look at phenomena that occur in a certain population using a cross sectional approach where data relating to variables will be collected at the same time. Data collection was carried out directly from respondents using questionnaire sheets. As a result, it was concluded that the effectiveness of health education on mothers' level of knowledge in providing sex education to school children aged 7-12 years showed that 30 mothers (90.9%) were in the high category and 3 mothers (9.1%) were in the medium category.